Performance analysis of screw turbine with varying design parameters - Khanal, Pawan; Duwadi, Swarnim; Pandey, Abhishek (Journal of Innovations in Engineering Education, 2024)
Small hydropower plays a crucial role in sustainable development, especially in rural areas of developing countries, by offering a cost-effective, local energy solution. This project focuses on optimizing Archimedean Screw Turbines (ASTs) through the analysis of key design variables: flow rate, inclination angle, and blade count. Evaluating twelve AST configurations across two flow rates (0.153 m³/s and 0.210 m³/s), three inclination angles (22.5, 24.5, and 27 degrees), and two blade setups (two and three) under a 4m head, we discovered optimal performance metrics. The three-blade model at a 24.5-degree angle and 0.210 m³/s flow rate achieved the highest efficiency of 75.38% and a torque of 1694.834 Nm, outperforming the two-blade configurations. Thus, the ideal AST design for boosting small hydropower efficiency is a three-bladed turbine at a 0.210 m³/s flow rate and 24.5-degree inclination, heralding a significant advancement for renewable energy access in remote communities.